Menstrual disorders - Disorders of sexual differentiation - Gutiérrez Pantoja, Rosario (2015)
Amenorrhea up when expected. Uterine bleeding in adolescents. PCOS in adolescent. Disorders of sexual differentiation. Dysfunctional uterine bleeding: alternative medical treatment.